Estimating Motives for Renting Shared Bicycles Using Multinomial Logistic Regression: A Case Study from the Slovak Republic - Stanislav Kubaľák; Jaroslav Mazanec; Marián Gogola (Applied Sciences)
This research aims to estimate the purposes for which bike-share users utilize shared bicycles from bike-sharing companies using selected predictors through multinomial logistic regression in Slovakia. The study seeks to provide a novel perspective on alternative transportation by addressing a gap in existing research, which has not previously focused on modeling the specific purposes of bicycle use. The final sample comprises 162 bike-share users out of more than 300 respondents. The results show that social status, bike-sharing company, and average distance are statistically significant input variables. Finally, we find that using shared bikes for recreation is more typical for employees with a traveled distance of up to 3 km from one of the two bike-sharing companies compared to the reference group (commuting to school). The paper contributes to better planning and management of bike-sharing systems.